REALIZATION OF VERBAL AND NON-VERBAL WORDS IN ADVERTISING TEXTS - Bektoshev Otabek Kodiraliyevich; Mamadaliev Hanifakhon Abdulkhamitovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article analyzes the features of the non-verbal component of the language of advertising in the formation of an advertising image. The necessity of taking into account, when compiling an advertising message, each element of the language of advertising, not only the verbal component, but also the non-verbal one, is revealed, since all components of the advertising message influence the formation of the advertising image.